Gesture Control Menggunakan IMU MPU 6050 Metode Kalman Filter Sebagai Kendali Quadcopter - Rudi Setiawan; Hendri Himawan Triharminto; Muhammad Fahrurozi (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The main task of the Indonesian Air Force is to uphold sovereignty in the territory ofIndonesia, so it requires human resources capable of defense equipment in accordance with the development of science and technology. One of the most important technologies is unmanned aircraft, so the research is expected to develop a drone control system with gestures, a communication system from radio to wireless and increase the accuracy of the gyroscope sensor with the Kalman filter algorithm. The system was built using a DJI Tello quadcopter drone with a gyroscope sensor using an IMU MPU 6050 and a processing system using Arduino Uno with Arduino Sketch software for kalman filter and wireless communication with Python. The system can control the drone with gestures for take off operations at an angle of 60 to 90 pitch angles, for landing at an angle of -60 to -90, for 362 data retrieval on the kalman filter method with a minimum variation of 0.00166 and a variation of 0.00564 in a range of 89.25 to 89.30. On roll with gesture to the right, if it is more than 30 to 90 and gesture to the left if it is more than -30 to -90 with a minimum variance of 0.0456 and a variance of 0.0141 at an angle of 90.42 to 90.44 of 362 experimental data samples, the system can communicate with the Wireless system.